THE ROLE OF PRIVATE SECTOR IN DEVELOPMENT PROGRAMME Of SUKAMULYA VILLAGE BAREGBEG SUBDISTRICT CIAMIS - Rira Nuradhawati (Jurnal Academia Praja, 2020)
In Sukamulya Village, Baregbeg Subdistrict, Ciamis Regency, at present there are several private sectors that are involved in determining the success of development in the village, the private sector was involved in an effort to accelerate rural development. The research itself was conducted in 2018 in the village of Sukamulya, Baregbeg district, Ciamis Regency. The method used in the study is a qualitative method through literature studies, field observations and very in-depth interviews with Sukamulya villagers. The involvement of private sector at Sukamulya Village make a big change in sukamulya village which had previously been underdeveloped is now a fairly developed village among rural villages in the sub-district. Baregbeg ciamis district, beside that can reduce unemployment there. So from the research we can know that the involvement of Private Sector determines the successful of develompment programme.